Physical Characteristics Evaluation of Kumpai Minyak Grass (Hymenachne amplexicaulis) Silage - Muhammad, Nur; Astuti, Andriyani; Utomo, Ristianto; Budi, S.P.S (Faculty of Animal Science, Universitas Gadjah Mada, ISSTAP 2017, 2017)
The study aimed to evaluate the nutritive value of Kumpai Minyak grass (Hymenachne amplexicaulis) silage. A total of 700g of Hymenachne amplexicaulis chopped with size 3-6 cm were used for silage by adding molasses levels (0, 2,5, and 5%) as well as the level of lactic acid bacteria (LAB) (0, 2, and 4 %). Silage inserted into a clear plastic bag and the air was removed. The silages were ripened for 21 days. Each treatment was done five times replication. The variables measured were physical quality and pH. Research data were analyzed by analysis of variance (ANOVA), if there was a significant difference between the treatments it will precede with Duncan’s Multiple Range Test. The physical quality characteristics of silage were generally good. The addition of LAB did not affect (P> 005) on pH (4,10 to 4,21) but the addition of molasses gave significantly affect (P <0.05) on pH (3,69 - 4,84). The combination between LAB level and molasses level with the best physical quality was found in 4% LAB and 5% molasses levels.